2013
DOI: 10.2337/dc13-1072
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Prognostic Value of Cardiovascular Autonomic Function in Coronary Artery Disease Patients With and Without Type 2 Diabetes

Abstract: OBJECTIVE Cardiovascular autonomic dysfunction is a common finding among patients with coronary artery disease (CAD) and type 2 diabetes (T2D). The reasons and prognostic value of autonomic dysfunction in CAD patients with T2D are not well known. RESEARCH DESIGN AND METHODS We examined the association between heart rate recovery (HRR), 24-h heart rate (HR) variability (SD of normal R-R interval [SDNN]), and HR turbulence (HRT), and echocardiographic parameters, metabolic, inflammatory, and coronary risk variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
(43 reference statements)
1
31
0
Order By: Relevance
“…We found that CRP levels were also independent predictors of higher NT-apoAI/apoAI ratio. Elevated CRP was found in patients with DM and those with cardiovascular disease 39 , and it carries prognostic value for cardiovascular events in CAD patients with DM 40 . Further investigations are needed to evaluate whether NT-apoAI/apoAI ratio can be an inflammatory biomarker in cardiovascular disease or inflammation contributes to higher NT-apoAI/apoAI ratio.…”
Section: Discussionmentioning
confidence: 99%
“…We found that CRP levels were also independent predictors of higher NT-apoAI/apoAI ratio. Elevated CRP was found in patients with DM and those with cardiovascular disease 39 , and it carries prognostic value for cardiovascular events in CAD patients with DM 40 . Further investigations are needed to evaluate whether NT-apoAI/apoAI ratio can be an inflammatory biomarker in cardiovascular disease or inflammation contributes to higher NT-apoAI/apoAI ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed exclusion criteria are described elsewhere in details. 12 For the present substudy, the patients with contraindicated exercise test (n ¼ 62) or incomplete follow-up data (n ¼ 118), without b-blocker medication (n ¼ 227), or those who had died because of noncardiovascular reasons (n ¼ 5) were excluded. The study was performed according to the Declaration of Helsinki, and the local committee of research ethics of the Northern Ostrobothnia Hospital District approved the protocol; all the subjects gave written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The findings are in line with those of Karjalainen et al, who found that the prognostic impact of autonomic function in CAD was very small in non-diabetic subjects. 30 Moreover, reduced HF power as well as LF power independently correlated with angiographic CAD, after controlling for age in patients with high Framingham risk or diabetes rather than in those without (Figures S1-S3). There was a significant improvement in risk reclassifications by modeling HRV in the prediction model of angiographic CAD in high Framingham risk patients.…”
Section: Hr Et Almentioning
confidence: 99%